Designing Social Media Index for Zakat Institutions (S/O 14212) - Sharif, Mohd Hisham; Saad, Ram Al Jafri; Abdullah, Zaimah; Mohd Ariff, Arifatul Husna; Md. Hussain, Md. Hairi; Khairudin, Norhaiza (UUM, 2023)
Purpose – This study aims to explore the factors of social media adoption by zakat institutions and use the findings to develop an index for Zakat institutions best practices. Design/methodology/approach – This study uses qualitative data as the main source of evidence as well as quantitative data for support and verification. Data were collected using semi-structured face-to-face interviews for the qualitative data and online survey for the quantitative data. Ten respondents from eight zakat institutions across Malaysia were interviewed and 150 respondents responded to the survey. Judgement sampling and snowballing techniques were used to select respondents. Data analysis was done in three phases, namely, data reduction, data display and conclusion confirmation. For the quantitative data, Partial Least Square method using SmartPLS was utilized for analysis. Findings – The findings of this study found perceived benefits, ease of use, accessibility, formalization, training, management push and indirect public push to be the determinant factors that contribute to the adoption of a social media application in zakat institutions. They are discussed and organized into a few groups under four categories, namely, technological, organizational and environmental contexts based on the TOE framework. Practical implications – Output from this study may be useful to the adoption champions within zakat institutions, such as decision-makers and marketing officers. These people can help to provide guidelines and steer managers to focus on the identified factors in this study when adopting social media. Social implications – The finding from this study may help to increase the efficiency of two-way communication between zakat institutions and the community. It was found that the adoption of social media improved communication activities with the public and better handling of negative perceptions towards zakat institutions. The findings proved that using social media applications in zakat institutions can help create a better organizational image for the public by publishing instant and continuous news feeds on activities that specifically cater to the need of the asnaf. This can alleviate negative perceptions that zakat institutions are only good in collecting money, but not effective in helping the poor. Originality/value – Previous zakat literature has focussed on different issues such as the determinants of zakat compliance behaviors, zakat fund management, distribution of funds, zakat information system and digital marketing; however, little is known about how and why zakat institutions adopt social media applications as a communication tool with the public.